USE OF CAPITAL TAX AND ITS APPLICATIONS IN THE DEMOCRAT PARTY’S ELECTION WORKS - Meral BALCI (Fırat University, 2019)
The capital tax, which was enacted in 1942, was issued to relieve the economically disadvantaged state of the World War II. Nevertheless, the content of this law and the negativities that have developed after its implementation have caused the RPP to be criticized severely. This tax, which the RPP applied not only to the non-Muslims but also to the Muslims, caused unrest because of the proportional injustice of the collection and the non-Muslims who were unable to pay the tax. Along with the difficult living conditions during the war, this injustice brought the people away from the RPP and opened the way to the ruling Democratic Party. Aim of this study is to examine the effects and usage of the tax and its imperfections on Democratic Party's electoral policies on the way to the Democratic Party's path to rule. In this context, it was observed that the tax was a significant instrument in Democratic Party's coming into power. The instruments of the study are official journals of the term, memoirs, books written on this subject and related news on daily newspapers.